x^3-10x^2+25x=

Simple and best practice solution for x^3-10x^2+25x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x^3-10x^2+25x= equation:


Simplifying
x3 + -10x2 + 25x = 0

Reorder the terms:
25x + -10x2 + x3 = 0

Solving
25x + -10x2 + x3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(25 + -10x + x2) = 0

Factor a trinomial.
x((5 + -1x)(5 + -1x)) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Subproblem 3

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Solution

x = {0, 5, 5}

See similar equations:

| 3(2-2y)=y-8 | | x+.5x=10000 | | 7r+3=4r-11 | | -x+3=10 | | 4x^2+25x+-21=y | | 168x+151.4y=2400 | | x+x+x=12+x | | 3x(8x-5)=0 | | 6+b+c=25 | | -x^4-2x^2+2=0 | | -0.59(d-1.5)=2.5 | | 1.2x+4.3=21-x | | 3x^2-2mx+m=0 | | 3=2x+3 | | 6+b+c=25-7 | | 4x*6+4/(65/6)=4 | | -5=2x+3 | | 8x=5(x-13) | | y=4[x-(2-x)]-7(x+1) | | 7x+1=-6x-25 | | 1=3(x-4)-(x-9) | | 7(x-8)-8(x-7)=x+7-(x-2) | | 13j+-9j+15=3 | | 6p-2-3p=17 | | 3n+1-16-n=20 | | 16v+-4v+-14=10 | | 8x+8=6x+44 | | 14x=x^2 | | 2y-9=10y+55 | | 8x-(2x-8)=62 | | 4a-5b=5 | | 5x-(x+4)=5+4(x-2) |

Equations solver categories